Síndrome de Leigh : descrição de um caso clínico e revisão teórica - Marinho, Joana Rita Marques (2014)
Leigh´s syndrome, also known as sub acute necrotising encephalomyelopathy, is a rare hereditary and neurodegenerative disorder. The clinical manifestations are heterogenic and usually arise during infancy. These are a translation of the focal, symmetrical and bilateral necrotic lesions within the central nervous system, mainly in the basal ganglia, thalamus and brainstem. Herein we can highlight the delay of the psychomotor development, the axial hypotonia and the movement disorder. Typically, there is a rise in the blood and cerebrospinal fluid levels of lactate. The cerebral magnetic resonance imaging scan reveals a prevailing involvement of the structures already approached. These are crucial findings to the syndromatic diagnosis.The majority of the cases results from nuclear DNA mutations with an autosomal recessive inheritance, leading to an enzymatic dysfunction of the respiratory chain, Coenzyme Q or of the pyruvate dehydrogenase complex. The approach undergoes a symptomatic control and it has a dismal prognosis. This paper will describe the case of a five year old child diagnosed with Leigh´s syndrome due to a SURF1 gene mutation, and it shall discuss the forms of clinical, laboratory and imaging presentation, diagnosis and treatment of the referred disorder.